A mild and metal-free synthesis of 2- and 1-alkyl/aryl/dialkyl-aminoquinolines and isoquinolines. Issue 13 (20th February 2020) - Nanaji, Yerramsetti; Kirar, Seema; Pawar, Sandip V.; Yadav, Ashok Kumar
Abstract : A synthetic strategy has been developed for synthesis of 2 and 1-aminoquinolines and isoquinolines from quinoline and isoquinoline- N -oxides, amines and triflic anhydride in acetonitrile at 0 °C to room temperature. Abstract : A simple synthetic strategy has been developed for the synthesis of 2- and 1-alkyl/aryl/dialkylaminoquinolines and isoquinolines from the easily available quinoline and isoquinoline- N -oxides, different amines, triflic anhydride as activating agent and acetonitrile as solvent in a one-pot reaction under metal-free conditions at 0 °C to room temperature.